If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1r = 12x Reorder the terms: -1r + 8x = 12x Solving -1r + 8x = 12x Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-8x' to each side of the equation. -1r + 8x + -8x = 12x + -8x Combine like terms: 8x + -8x = 0 -1r + 0 = 12x + -8x -1r = 12x + -8x Combine like terms: 12x + -8x = 4x -1r = 4x Divide each side by '-1'. r = -4x Simplifying r = -4x
| Ln(x^3+10x^2)-ln(x)=ln(24) | | 42a-9= | | 10x-(2x+9)=-3(15-x) | | 1/5A-3=0 | | 1.13x=20 | | .002y+.12(6000-y)=.40y | | 3/4(k=2)=9 | | 6y+2=7y-11 | | 6x^3(-2x^5)= | | fx=-3x^2-1x | | 2m+2=m+7 | | 21=180m | | 18=450b | | 6xy/6xy | | w^2+4w=800 | | .05x+0.25(40+x)+0.10(3x)=17.20 | | 3x-66=90+9x | | x-1145141919810=89464 | | 1/3•54 | | w^2+4w+800=0 | | 300+0.05(90000)= | | -5(6-b)=35 | | 24x^2-5x-10=0 | | F(x)=3x^2+12x+16 | | 22=2-3x | | 25x-10+12x-15x=36 | | 5-(1-5x)+5(-8x-2)=-4x-8x | | 500+0.10s=300+0.05s | | (4xy^4/x^-5y^-3)^-2 | | -45+6x=21 | | 45+6x=21 | | Kn+34=-2(1-7n) |